Interaction of Serum-Derived and Internalized C3 With DNA in Human B Cells—A Potential Involvement in Regulation of Gene Transcription - Kremlitzka, Mariann; Nowacka, Alicja A.; Mohlin, Frida C.; Bompada, Pradeep; De Marinis, Yang; Blom, Anna M. (Frontiers in Immunology, 2019)
Beside its classical role as a serum effector system of innate immunity, evidence is accumulating that complement has an intracellular repertoire of components that provides not only immune defense, but also functions to maintain cellular homeostasis. While complement proteins, mainly the central component C3, have been detected in B cells, its exact function and source remain largely unexplored. In this study, we investigated the expression and origin of intracellular C3 in human B cells together with its role in B cell homeostasis. Our data provide evidence that endogenous expression of C3 is very low in human B cells and, in accordance with the recent publication, the main origin of intracellular C3 is the serum. Interestingly, we found that both serum-derived and purified C3 are able to enter the nucleus of viable B cells, suggesting its potential involvement in regulation of gene transcription. ELISA, gel shift assay, confocal microscopy and chromatin immunoprecipitation proved that C3 and C3a strongly bind to nuclear DNA, and among the interacting genes there are key factors of lymphocyte development and differentiation. The strong interaction of C3 with histone proteins and its potential ability to induce chromatin rearrangement suggest that C3/C3a might regulate DNA transcription via chromatin remodeling. Our data reveal a novel, hitherto undescribed role of C3 in immune cell homeostasis, which further extends the repertoire how complement links innate and adaptive immunity and regulates basic processes of the cells.